Post Trauma: Medicalization and Damage to Social Reform - Lovrod, Marie; Ross, Lynda R. (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
While posttraumatic stress disorder has catalogued symptoms of trauma, the resulting de-contextualization has served to create complicity with power systems that contribute to the production of trauma. Women are overrepresented as targets of violence and as recipients of this diagnosis.